(untitled) (Yesterday & Today Journal for History Education in South Africa and abroad, 2022)
This article is concerned with an aspect of the impact of Covid-19 on the higher education sector. It examines the impact of group work in remote university teaching and learning in the context of Covid-19 imposed lockdowns in South Africa. When the pandemic broke out few were prepared for its worst excesses in terms of lives lost, impact on health facilities, economies and higher education. To limit its spread, lockdowns were imposed in many countries across the world, limiting in person interaction which affected various aspects of human contact, not least in university education. Taken away from campuses, universities in South Africa, as elsewhere, were forced not only to adapt to online teaching, but to be inventive in the methods used to retain student participation and engagement. While technology has been heralded as the solution to the global crisis in terms of teaching, there are other concerns that affect the wellbeing of students that also require attention. Using research conducted with staff and students at one South African university, this article considers the pandemic classroom with its online and remote mode of instruction, and takes specific cognisance of what is lost as a result of this form of engagement in terms of the psychological and emotional impact of isolation on students in the tertiary education sector. Within this context, it assesses whether the use of group work within a university environment is a possible means to try and bridge this digital divide or is this option merely a case of groping in the digital ditch.